Awareness of Social Networking Services Among the Faculty Members of Degree Colleges of Jammu Division J&K India - Gupta, Sangita; Seth, Anuradha (Journal of Information and Knowledge, 2015)
Participation with technology to handle social, cultural and educational activities has become the mainstream for communication and information sharing method for many people in the past several years. Educational institutions, the first doorstep towards shaping knowledge, have changed radically byadopting such communication and information sharing skills as the paramount way to enhance educational products. Mastering of information technology has promoted an environment of healthy education system world over. Teachers with broad vision, adopting new innovations and skills, can improve the fate of nation by educating millions. In particular, social networking servicessuch as Web 2.0 based participatory technological services that have formed a class of interactive teaching and learning, processing instant information for furthering knowledge. These services are becoming the key to information and communication in the world. Realizing that social networking services may have the ability to promote both, active learning and collaboration, the educationists both tutor and taught are eyeing this potential as better information sharing tools to be utilised in education. This study attempts to find out the level of awareness of social networking sites among a sample of 300 faculty members of Government Degree Colleges of Jammu Division to determine their involvement with the emerging trends and tools to enhance academic performance. The study highlights the problems encountered by the participants and suggests some remedial measures for improving awareness.